Penerapan Manajemen Kesiswaan di Madrasah Diniyah Haji Ya’qub Lirboyo Kota Kediri - Wildan Habibi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
Madrasah as part of educational institution that appear in Indonesia, that madrasah has been long participated in improving human resources and educating life of the Indonesian people. The other hand madrasah is madrasah diniyah. As part of Islamic educational institutions, madrasas diniyah also manages several things that related to the educational components such as the management of student or learner. This research used the descriptive-qualitative of paradigm approach. The results of the research showed that The first Diniyyah Madrasah Haji Ya’qub has been able to implement some things that become part of the student management in according to existing regulations. The second there are problems faced both diniyyah Madrasah Haji Ya’qub, in implementing student management such as a) There are many students who have not been able to recognize to the social environment in the location of madrasah. b) The students’ interest to understand the lessons is low. c) The students’ attendance rate is less than the maximum. The third to face those problems madrasah diniyah haji ya’qub has some efforts as follows: a) Urge to all teachers to instruct their students to participate to the events to know the students’ physical and social environment. b) Instructed to the teachers to pay attention to their students to be active in all of activities of madrasah c) The functionaries give the warning and punishment to the students who are not going to School or discussion.